Flip-based e-comic media: Enhancing HOTS in elementary mathematics learning - Hapsari, Bintang; Nugraheni, Nursiwi (Indonesian Journal of Science and Mathematics Education, 2024)
This study aims to develop a flip-based e-comic as a learning medium and analyze its impact on the HOTS (Higher-Order Thinking Skills) of fourth-grade students in mathematics, specifically on the topic of calculating the area of plane figures. The study employs the Research and Development method using the Borg and Gall model. Data analysis techniques include media feasibility tests, t-tests, and N-Gain tests. The results indicate that the e-comic is highly feasible for use, as evidenced by feasibility ratings from media experts (90%), content experts (89.2%), and language experts (87.5%). Based on the t-test, the e-comic was proven effective in learning, with a sig. (2-tailed) value of 0.000 < 0.05, indicating that Ho is rejected and Ha is accepted. Furthermore, the N-Gain test results show an improvement in students' abilities, with scores of 0.7164 for the small scale and 0.8307 for the large scale, both categorized as high. Thus, the e-comic positively impacts students' ability to solve HOTS questions. This study implies the provision of an alternative learning medium that supports the development of students' higher-order thinking skills while facilitating educators' integration of technology into modern learning practices.